2018
DOI: 10.3177/jnsv.64.385
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D Is Associated with Kidney Function: The Dong-gu Study

Abstract: Although the kidneys play a leading part in the biosynthesis of vitamin D, there is no consensus regarding the relationship of the vitamin D concentration with kidney function. Thus, we aimed to estimate the correlation among 25-hydroxyvitamin D (25(OH)D), estimated glomerular filtration rate (eGFR), and albumin/creatinine ratio (ACR) in participants aged $50 y in Korea. This study consisted of 9,166 people who participated in a basic survey of the Dong-gu Study. Following an overnight fast, the blood and urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Blood levels of 25-hydroxyvitamin D are considered indicative of human vitamin D status and can be taken to represent bone health and as an independent predictor of several chronic diseases [9,36]. Evidence had shown that 25-hydroxyvitamin D deficiency is related to albuminuria [9,10], impaired renal function [11], the need for long-term dialysis, and all-cause mortality [13]. Regarding the modulation of vascular functions, in vitro studies have demonstrated that 1,25-dihydroxyvitamin D can affect the proliferation of vascular smooth muscle cells and impair endothelium-dependent vasodilation because of the decreased bioavailability of vasodilators [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood levels of 25-hydroxyvitamin D are considered indicative of human vitamin D status and can be taken to represent bone health and as an independent predictor of several chronic diseases [9,36]. Evidence had shown that 25-hydroxyvitamin D deficiency is related to albuminuria [9,10], impaired renal function [11], the need for long-term dialysis, and all-cause mortality [13]. Regarding the modulation of vascular functions, in vitro studies have demonstrated that 1,25-dihydroxyvitamin D can affect the proliferation of vascular smooth muscle cells and impair endothelium-dependent vasodilation because of the decreased bioavailability of vasodilators [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…It has an established role in mineral homeostasis and musculoskeletal function and is also known to exert extra-skeletal effects, including modulation of endothelial function, immune function, inflammatory responses, and cell cycle regulation [9]. Deficiencies in 25-hydroxyvitamin D are associated with albuminuria [9,10] and impaired renal function in the general population [11] and all-cause mortality and kidney failure requiring long-term dialysis in pre-diabetic and DM patients [12,13]. Therefore, the reports of KDIGO (Kidney Disease: Improving Global Outcome) recommends regular measurement of serum levels to ensure sufficient vitamin D levels in patients with stage 3-5 CKD [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between 25(OH)D and kidney function has been controversial. Studies have shown that 25(OH)D has no protective effect on kidney function, and even has the opposite effect ( 7 , 8 ). There were even case reports of acute kidney failure caused by the use of vitamin D drops ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that even though 25(OH)D levels were sufficient, they did not seem to have the ability to protect kidney function ( 7 ). In addition, with increasing 25(OH)D levels, kidney function represented by eGFR significantly decreased ( 8 ).…”
Section: Introductionmentioning
confidence: 99%